Sexual and reproductive health of low income adolescence girls in Nepal: can education be a catalyst? - Hamal, Prabha Kumari (Economic Journal of Development Issues, 2012)
Using data from five districts of Mid-Western and Far-Western Development Region, this paper reaches to conclusion that education has significant and influential roles in determining the sexual and reproductive health of adolescence girls, particularly of those who are from low income families. A rough ‘U’ shaped relationship between education and reporting of health problems and gender-based violence was observed. Key words: Sexual and reproductive health; Low income adolescence; Girls; Nepal; Education; Catalyst Economic Journal of Development Issues Vol. 11 & 12 No. 1-2 (2010) Combined Issue Page: 92-98 Uploaded date: 10 April, 2012